Identifying vulnerabilities in communication in the emergency department. Issue 9 (21st August 2009) - Redfern, E; Brown, R; Vincent, C A
Abstract : Background: Communication in the emergency department (ED) is a complex process where failure can lead to poor patient care, loss of information, delays and inefficiency. Aim: To describe the investigation of the communication processes within the ED, identify points of vulnerability and guide improvement strategies. Methods: The Failure Mode Effects Analysis (FMEA) technique was used to examine the process of communication between healthcare professionals involved in the care of individual patients during the time they spent in the ED. Results: A minimum of 19 communication events occurred per patient; all of these events were found to have failure modes which could compromise patient safety. Conclusion: The communication process is unduly complex and the potential for breakdowns in communication is significant. There are multiple opportunities for error which may impact on patient care. Use of the FMEA allows members of the multidisciplinary team to uncover the problems within the system and to design countermeasures to improve safety and efficiency.